Visceral leishmaniasis complicated by hemophagocytic lymphohistiocytosis: A case report from a nonendemic area - Anwar I. Joudeh; Hussein A. Elsiddig Awadelkarim; Mohammadshah Isam Gul; Mahmoud Salm Elayana; Dina Sameh Soliman; Aliaa Amer; Musaed Alsamawi (Clinical Case Reports, 2023)
Key Clinical Message Visceral leishmaniasis and hemophagocytic lymphohistiocytosis share many features in common and may coincide in the same patient. Timely diagnosis and management of visceral leishmaniasis could save patients from unnecessary toxic treatment. Abstract Visceral leishmaniasis and hemophagocytic lymphohistiocytosis share many clinical features in common and may coexist in the same patient. Visceral leishmaniasis should be promptly ruled out in patients coming from endemic areas before starting immunosuppressive therapy for hemophagocytic lymphohistiocytosis. The mainstay treatment, in this case, is anti‐leishmania medications preferably liposomal amphotericin‐B.